The Influence of Leadership and Apparatus Performance on the Quality of Public Services and Impact on Society Satisfaction - Rizanuddin, Hafni (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aimed to analyze leadership factors and their effect on the quality of public services and their impact on society satisfaction. This research was conducted in Panyingkirian District, Majalengka Regency, West Java Province, Indonesia. This research is quantitative, and the analysis technique used is path analysis. The sample in this study used multistage random sampling, which was divided between the Rukun Warga (RW) and the Rukun Tetangga (RT) with 305 respondents from the society in the village Panyingkiran District. Sources of data in this study are primary data and secondary data with data collection techniques through research questionnaires distributed to respondents. The results showed that leadership, apparatus performance, quality of public services, and society satisfaction were in the moderate to good category. The results of hypothesis testing indicate that leadership and apparatus performance have a positive and significant effect on the quality of public services, and the quality of public services impacts society satisfaction.